The E3 Ubiquitin Ligase IDOL Induces the Degradation of the Low Density Lipoprotein Receptor Family Members VLDLR and ApoER2 - Hong, Cynthia (AMER SOC BIOCHEMISTRY MOLECULAR BIOLOGY INC, 2024)
10.1074/jbc.M110.123729